Distributed Lag Non-Linear Models for the impact of heat waves on elderly people living in the regions of central-eastern Italy - Roberta Sorbi; Maria Simonetta Bernabei (Epidemiology, Biostatistics and Public Health, 2025)
Background: Prolonged periods of extreme heat, usually referred to as heat waves, have a significant impact on health, especially in the most vulnerable populations. In the present study, we investigated the effect of heat waves on mortality in the elderly population living in the regions of central-eastern Italy.